2019
DOI: 10.3390/w11040796
|View full text |Cite
|
Sign up to set email alerts
|

Time Domain Simulation of Damage Flooding Considering Air Compression Characteristics

Abstract: An accurate analysis of the entire flooding process is critical to assess the damaged stability when a ship encounters distressed accidents such as collision, stranding, or grounding. Among many factors affecting the flooding process and damaged stability, the complex effect of air compression is significant and worthy of further research. In this paper, through establishing scenarios of the damage flooding for a cruise ship, the commercial software CD Adapco STARCCM+ is applied to perform time domain simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In the simulation process, in order to eliminate the composite influence arising from the air compressibility, an appropriate ventilation hole is constructed on the upper deck. In [24][25][26][27], it has the side view and body lines of the ship model, and Table 1 presents the principal dimensions of the ship model [23]. The created damaged compartment is located near the bow.…”
Section: Model Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the simulation process, in order to eliminate the composite influence arising from the air compressibility, an appropriate ventilation hole is constructed on the upper deck. In [24][25][26][27], it has the side view and body lines of the ship model, and Table 1 presents the principal dimensions of the ship model [23]. The created damaged compartment is located near the bow.…”
Section: Model Descriptionmentioning
confidence: 99%
“…In the simulation process, in order to eliminate the composite influence arising from the air compressibility, an appropriate ventilation hole is constructed on the upper deck. In [24][25][26][27], it has As shown in Figure 5, two comparative damage scenarios are modeled separately. It can be found that the scenarios are specific to the location of the damage opening.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reduce the effect of air compression on the flooding process, the decks and bulkheads are equipped with ventilation holes to ensure that the trapped air can escape from the flooded compartments. For a more realistic simulation of the hydrodynamic phenomenon due to air compression, the flooded compartments should be characterized with appropriate ventilation restrictions [14][15][16]22]. It can be found that different internal layouts result in distinct flooding forms.…”
Section: Description Of Dtmb Model 5415mentioning
confidence: 99%
“…The flooding of a 2D section of a Ro-Ro ship in forced heave and roll motions was modelled. XinLong, et al [14] focused on the application of commercial software STAR-CCM+ Reynolds-Averaged Navier-Stokes (RANS) solver for analyzing the effect of air compression on the flooding process. Cao, et al [15] proposed a multi-phase SPH model combined with a dummy boundary method, considering air effect on the responses of the damaged ship in the dynamic flooding process.…”
Section: Introductionmentioning
confidence: 99%